The prevalence of overweight and obesity and the assessment of associated risk factors among school-aged adolescents in Kandahar City, Afghanistan - Mohibullah Mako; Najeebullah Rafiqi; Azizullah Noori; Bilal Ahmad Rahimi (PLoS ONE, 2025)
Background Adolescent obesity is a growing global public health issue, contributing to the early onset of non-communicable diseases like type 2 diabetes and cardiovascular disorders. In South Asia, including Afghanistan, urbanization and lifestyle changes have triggered a nutritional shift marked by unhealthy diets and reduced physical activity. Yet, research on adolescent obesity in Afghanistan, particularly in urban areas like Kandahar, is scarce. Kandahar’s rapid development and cultural diversity necessitate an assessment of obesity prevalence and associated risk factors among school-going adolescents to inform health policies. Methods This cross-sectional analytical study was conducted among 384 male adolescents (aged 10–19 years) in Kandahar City between February and July 2023. Height and weight were measured to calculate BMI, which was classified using CDC BMI-for-age percentiles. Results The prevalence of overweight/obesity was 13.3%. Multivariate analysis identified parental obesity (+10.4; p = 0.002), screen time ≥30 minutes/day (+8.8; p = 0.011), and consumption of school canteen food (7.8; p = 0.037) as significant predictors of higher BMI percentiles. Conclusion Targeted interventions involving Family-centered education, promotion of active lifestyles, and regulation of school nutrition are critical to address adolescent obesity in this setting. Findings are limited to male adolescents due to cultural constraints and may not be generalizable to females.